Effects of dynamic ultra-high pressure homogenization on the structure and functional properties of casein - Wang, Chunyan; Ma, Yaping; Liu, Benguo; Kang, Zhuangli; Geng, Sheng; Wang, Jianan; Wei, Lipeng; Ma, Hanjun (International Journal of Agricultural and Biological Engineering, 2019)
Dynamic ultra-high pressure homogenization (UHPH) is a novel high-pressure processing technique. In this study, the effects of dynamic UHPH on the structure and functional properties of casein were systematically investigated. It was found that the functional properties of casein changed with dynamic UHPH treatment, and the treatment at 150 MPa could significantly improve casein aqueous solubility, foaming and emulsifying properties. These functional improvements could be attributed to its structural changes, since the dynamic UHPH treatment could change the secondary structure, promote the interchange reaction between the disulfide bond and the sulfhydryl group, and increase the surface hydrophobicity. The obtained results could broaden the application of casein and provide ideas for the non-thermal processing of proteins. Keywords: casein, dynamic ultra-high pressure homogenization, functional properties, secondary structure, hydrophobicity, non-thermal processing DOI: 10.25165/j.ijabe.20191201.3015 Citation: Wang C Y, Ma Y P, Liu B G, Kang Z L, Geng S, Wang J N, et al. Effects of dynamic ultra-high pressure homogenization on the structure and functional properties of casein. Int J Agric & Biol Eng, 2019; 12(1): 229–234.